Projeto mecânico e análise de uma balança utilizada em experimentos com máquinas de lavar roupas - Cruz Neto, José Oliveira (Universidade Federal de São Carlos, 2024)
Noise and vibration control plays an important role in the development of household appliances and, as society evolves, this equipment becomes increasingly important in daily life. Consequently, increasingly rigorous standards are imposed by consumers so that the product meets its required performance and improvements in quality of life. On the other hand, meeting these requirements becomes an increasingly complicated task as it requires continuous improvement in control and measurement systems and, often, commonly market available devices are not capable of meeting the requirements imposed by development teams. With this in mind, the present work develops the mechanical design of a weighing scale that will be used in experiments with horizontal axis washing machines. The objective is to obtain equipment that has the smallest possible displacement at the corners of the platform so that the dynamics of the scale does not interfere with the acquisition during experiments.
Mechanical design and analysis of a scale used in experiments with washing machines
Keywords: Projeto mecânico; Lavadora de roupas; Balança; Mechanical design; Washing machine; Weighing scale; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS